L’indirection : Procédé d’expression et de persuasion en communication publique - Gauthier, Gilles (Canadian Journal of Applied Linguistics, 2010)
The article is about the indirection process presented in Searle’s and Vanderveken’s theory of speech acts: the performance of a primary speech act by means of the accomplishment of a secondary speech act. Considering the typology of speech acts and their performance conditions, the article first proposes an explicit definition of indirection. Following from this definition, several mechanisms for indirection are identified, i.e. different ways of performing an indirect speech act. The article then discusses the indirection mechanisms used in advertising (five mechanisms) and in political communication (six mechanisms). Finally, a number of reasons are given to explain the relative importance of the use of indirection in these two fields of public communication according to their persuasive goal.